Simple sequence repeats together with mismatch repair deficiency can bias mutagenic pathways in Pseudomonas aeruginosa during chronic lung infection - Moyano, Alejandro J. (2013)
Fil: Moyano, Alejandro J. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Departamento de Química Biológica; Argentina.